2022
DOI: 10.3390/ijms23094600
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Long Noncoding RNA Modified by m6A Methylation in Oxidative and Glycolytic Skeletal Muscles

Abstract: N6-methyladenosine (m6A) is the most common modification in eukaryotic RNAs. Accumulating evidence shows m6A methylation plays vital roles in various biological processes, including muscle and fat differentiation. However, there is a lack of research on lncRNAs’ m6A modification in regulating pig muscle-fiber-type conversion. In this study, we identified novel and differentially expressed lncRNAs in oxidative and glycolytic skeletal muscles through RNA-seq, and further reported the m6A-methylation patterns of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 83 publications
1
10
0
Order By: Relevance
“…Thus, we reassembled the transcripts of all samples using MeRIP-seq and RNA-seq data and stream neural network algorithms in this study. Our study was the first evidence to identify the m 6 A-methylated lncRNAs dynamic alteration during Longissimus dorsi muscle development in cattle-yak, which results were consistent with the results of m 6 A-lncRNA in mice [ 40 ] and pigs [ 39 ]. Moreover, gene expression levels can be regulated by m 6 A modification, for example, METTL14 knockdown can enhance the expression level of XIST through decreasing the m 6 A modification of XIST , and m 6 A-methylated XIST can also be recognized by YTHDF2 to mediate XIST degradation [ 72 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, we reassembled the transcripts of all samples using MeRIP-seq and RNA-seq data and stream neural network algorithms in this study. Our study was the first evidence to identify the m 6 A-methylated lncRNAs dynamic alteration during Longissimus dorsi muscle development in cattle-yak, which results were consistent with the results of m 6 A-lncRNA in mice [ 40 ] and pigs [ 39 ]. Moreover, gene expression levels can be regulated by m 6 A modification, for example, METTL14 knockdown can enhance the expression level of XIST through decreasing the m 6 A modification of XIST , and m 6 A-methylated XIST can also be recognized by YTHDF2 to mediate XIST degradation [ 72 ].…”
Section: Discussionsupporting
confidence: 89%
“…In addition to the ubiquitous m 6 A modifications on mRNAs, m 6 A modifications on lncRNAs have also attracted more and more attention from researchers. Recent studies have revealed the promotion of m 6 A modification on lncRNA in the muscle development and muscle fiber type conversion [ 14 , 39 , 70 , 71 ], and some researchers reported the dynamic changes of m 6 A-methylated lncRNAs during skeletal muscle formation in mouse C2C12 myoblast cell line [ 40 ]. However, there was still no report about the m 6 A methylation characteristics of lncRNAs in the muscle development stage of cattle-yak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study revealed the difference in phenotypic traits in SOL and EDL and evidenced that SOL and EDL are typical oxidative and glycolytic muscle tissues, respectively [ 31 ]. In the present study, the transcriptomes of EDL and SOL muscles were examined to reveal the landscape of AS changes across oxidative and glycolytic muscles.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study reported m6A methylome profiling of lncRNA in pig extensor digitorum longus (EDL) and soleus (SOL) muscles [ 31 ]. In the present study, we further integrated RNA-seq and methylated RNA immunoprecipitation sequencing (MeRIP-seq) for the comprehensive analysis of AS events and m6A methylation pattern.…”
Section: Introductionmentioning
confidence: 99%